THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE EFFICIENCY OF THE OIL AND FAT INDUSTRY: PROBLEM ANALYSIS, INNOVATIVE SOLUTIONS, AND ASSESSMENT METHODOLOGIES (International journal of artificial intelligence, 2026)
Unlike superficial application of AI, AI implementation implies sustainable implementation, scaling, and profit-making from it. This is achieved through a coordinated system of data, competencies, and processes. In the oil and fat sector, the development stage and ownership structure influence how effectively AI implementation results can be measured and evaluated. Triangle-shaped graphical elements depicting the relationship between potential and results illustrate contradictions, such as efficiency growth, which can lead to increased energy consumption. Unlike superficial application of AI, AI implementation implies sustainable implementation, scaling, and profit-making from it. This is achieved through a coordinated system of data, competencies, and processes. In the oil and fat sector, the development stage and ownership structure influence how effectively AI implementation results can be measured and evaluated. Triangle-shaped graphical elements depicting the relationship between potential and results illustrate contradictions, such as efficiency growth, which can lead to increased energy consumption.